OTULIN restricts Met1-linked ubiquitination to control innate immune signaling. - Fiil, B; Damgaard, R; Wagner, SA; Keusekotten, K; Fritsch, M; Bekker-Jensen, S; Mailand, N; Choudhary, C; Komander, D; Gyrd-Hansen, M (2013)
Conjugation of Met1-linked polyubiquitin (Met1-Ub) by the linear ubiquitin chain assembly complex (LUBAC) is an important regulatory modification in innate immune signaling. So far, only few Met1-Ub substrates have been described, and the regulatory mechanisms have remained elusive. We recently identified that the ovarian tumor (OTU) family deubiquitinase OTULIN specifically disassembles Met1-Ub. Here, we report that OTULIN is critical for limiting Met1-Ub accumulation after nucleotide-oligomerization domain-containing protein 2 (NOD2) stimulation, and that OTULIN depletion augments signaling downstream of NOD2. Affinity purification of Met1-Ub followed by quantitative proteomics uncovered RIPK2 as the predominant NOD2-regulated substrate. Accordingly, Met1-Ub on RIPK2 was largely inhibited by overexpressing OTULIN and was increased by OTULIN depletion. Intriguingly, OTULIN-depleted cells spontaneously accumulated Met1-Ub on LUBAC components, and NOD2 or TNFR1 stimulation led to extensive Met1-Ub accumulation on receptor complex components. We propose that OTULIN restricts Met1-Ub formation after immune receptor stimulation to prevent unwarranted proinflammatory signaling.